2005
DOI: 10.1161/circulationaha.105.549071
|View full text |Cite|
|
Sign up to set email alerts
|

KCNH2 -K897T Is a Genetic Modifier of Latent Congenital Long-QT Syndrome

Abstract: Background-Clinical heterogeneity among patients with long-QT syndrome (LQTS) sharing the same disease-causing mutation is usually attributed to variable penetrance. One potential explanation for this phenomenon is the coexistence of modifier gene alleles, possibly common single nucleotide polymorphisms, altering arrhythmia susceptibility. We demonstrate this concept in a family segregating a novel, low-penetrant KCNH2 mutation along with a common single nucleotide polymorphism in the same gene. Methods and Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
166
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 228 publications
(174 citation statements)
references
References 43 publications
7
166
1
Order By: Relevance
“…Therefore genes that contribute to sudden cardiac death occurrence have to be separated from genes that lead to associated conditions. Secondly, even for the so-called "monogenic syndromes" such as the long QT syndrome, there may be additional modifier genes that are involved (50,94). For the complex phenotype of overall sudden cardiac death, it is quite likely that for an individual patient, screening may have to be conducted for a panel of genes instead of a single gene.…”
Section: Potential Role Of Genetic Factors In Predicting Risk Of Suddmentioning
confidence: 99%
“…Therefore genes that contribute to sudden cardiac death occurrence have to be separated from genes that lead to associated conditions. Secondly, even for the so-called "monogenic syndromes" such as the long QT syndrome, there may be additional modifier genes that are involved (50,94). For the complex phenotype of overall sudden cardiac death, it is quite likely that for an individual patient, screening may have to be conducted for a panel of genes instead of a single gene.…”
Section: Potential Role Of Genetic Factors In Predicting Risk Of Suddmentioning
confidence: 99%
“…The concept of modifier genes, including compound heterozygosity 26 and the addition of single-nucleotide polymorphisms (SNPs) 27,28 to LQTS mutations, has been proposed to explain the phenomenon of phenotypic heterogeneity. 29 Although modifier genes have previously been reported in the context of amplifying the effect of LQTS mutations, 26 -28 a recent study has provided some evidence that SNPs might ameliorate the clinical phenotype of a LQTS mutation.…”
Section: Potential Role Of Modifying Factorsmentioning
confidence: 99%
“…Meanwhile, our research group has identified rather serendipitously a first modifier gene for the severity of LQTS [48]. This finding had been preceded by our quantification [49] of the curious phenomenon of 'double' or 'two independent mutations', by which it appears that approximately 5% of LQTS patients inherit two relatively mild mutations by the parents (often asymptomatic) and then manifest severe LQTS, and by the observation by Westenskow et al [50] that two to three individuals from one family carrying one LQTS mutation and the rare single nucleotide polymorphism (SNP) D85N (on KCNE1) had more severe clinical manifestations.…”
Section: Modifier Genesmentioning
confidence: 99%